Insects found in birds’ nests from Argentina. Cyanoliseus patagonus (Vieillot, 1818) [Aves: Psittacidae], with the description of Cyanolicimex patagonicus, gen. n., sp. n., and a key to the genera of Haematosiphoninae (Hemiptera: Cimicidae) - Iorio, Osvaldo Di; Turienzo, Paola; Masello, Juan; Carpintero, Diego L. (Zootaxa, 2010)
The Burrowing Parrot, Cyanoliseus patagonus (Vieillot, 1817) [Aves: Psittacidae], is one of the most southern Neotropical parrots. They require sandstone, limestone, or earth cliffs where they excavate their colonial nest-burrows. Adult C. p. patagonus excavate their own nest-burrows, most of them about 1.5 m deep. Each burrow is occupied by a single pair that lay one clutch of two to five eggs per year, directly on the sand of the breeding chamber. The breeding birds abandon the place until the start of the next breeding attempt in the following year. Burrow nests from Río Negro province (Argentina) are inhabited by two ectoparasitic insects, the flea Hectopsylla narium (Siphonaptera: Pulicidae), and Cyanolicimex patagonicus, gen. n., sp. n. (Hemiptera: Cimicidae). The Rio Negro province is the southernmost known limit for Haematosiphoninae in the Western Hemisphere, and C. patagonicus is the third Haematosiphoninae with a Psittacidae bird as host. As the South American genera of Haematosiphoninae cannot be separated using the available key due to unsatisfactory characters, the proposition of new characters for the identification of the four South American genera, together with the corresponding modifications to the key, are presented.